Kajian Etnobotani Tumbuhan Obat oleh Etnis Melayu di Desa Bagan Percut, Sumatera Utara - Banurea, Aisyah; Susilo, Ferdinand; Nasution, Jamilah; Rahmiati, Rahmiati; Riyanto, Riyanto (Universitas Medan Area, 2025)
Medicinal plants have long been used in traditional medicine as part of healing and disease prevention practices. The Malay ethnic group possesses inherited ethnobotanical knowledge regarding the use of medicinal plants. This study aims to identify the types of plants used as medicine and their applications by the Malay community in Bagan Percut Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. A qualitative and quantitative descriptive approach was employed through interviews with 50 respondents and 10 key informants possessing local knowledge of medicinal plants. The results revealed 65 medicinal plant species belonging to 35 sukues, with the dominant ones being Zingiberaceae (6 species), Solanaceae (5 species), and Fabaceae (5 species). The most frequently used plant parts were leaves (46%), fruits (28%), and rhizomes (9%). The most common method of preparation was boiling (29%), while the most common mode of use was oral consumption (48%). Herbaceous plants constituted the most utilized growth form (31%). The purposes of plant utilization included treatment (61.53%), care (24.6%), and general health improvement (13.8%). This study highlights the importance of preserving traditional ethnobotanical knowledge among the Malay community.